2018
DOI: 10.1016/j.jgeb.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic effects of silver and gold nanoparticles on Allium cepa roots

Abstract: The present study evaluates the cytogenetic effects of both silver and gold nanoparticles on the root cells of Allium cepa. In this study, the root cells of Allium cepa were treated with both gold and silver nanoparticles of different concentrations (1 mg/L, 5 mg/L and 10 mg/L) along with control for 72 h. Experimental results revealed that after 72 h of exposure, a significant decrease in mitotic index (MI) from 68% (control) to 52.4% (1 mg/L), 47.3% (5 mg/L) and 41.4% (10 mg/L) for gold nanoparticles and 57.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 34 publications
5
19
0
Order By: Relevance
“…Figures 6 and 7 present the charts of logarithmic dependence A = a*ln(C) + b of the shoot growth activity on the concentration of Ag/Au nanoparticles and G. urbanum L extract respectively for lupine, corn, flax, Chia, tomato and garden cress. The obtained study results confirm that metal nanoparticles can exhibit both positive and negative effect on higher plants [27]. One example of that are the studies demonstrating the impact of silver nanoparticles on crops like barley [30], wheat [31], Brassica [32] and radish [33], in which no significant negative impact of nanoparticles was found on any plant species.…”
Section: Determination Of the Inhibitory Concentration 50% (Ic50)supporting
confidence: 73%
See 1 more Smart Citation
“…Figures 6 and 7 present the charts of logarithmic dependence A = a*ln(C) + b of the shoot growth activity on the concentration of Ag/Au nanoparticles and G. urbanum L extract respectively for lupine, corn, flax, Chia, tomato and garden cress. The obtained study results confirm that metal nanoparticles can exhibit both positive and negative effect on higher plants [27]. One example of that are the studies demonstrating the impact of silver nanoparticles on crops like barley [30], wheat [31], Brassica [32] and radish [33], in which no significant negative impact of nanoparticles was found on any plant species.…”
Section: Determination Of the Inhibitory Concentration 50% (Ic50)supporting
confidence: 73%
“…According to the literature, small nanoparticles (< 50 nm) are able to easily penetrate and pass into the lymphatic system. Subsequently, they can reach and harm the vital organs and body tissues [27]. Nanoparticles of various sizes are taken up by plants, translocated to shoots and accumulated in various aerial parts, which increases the possibility that they will be cycling in the ecosystem through various trophic levels.…”
Section: Determination Of the Inhibitory Concentration 50% (Ic50)mentioning
confidence: 99%
“…Table 1 summarizes the cytotoxic and genotoxic response registered after the exposure of Allium cepa to different concentrations of diverse AgNPs formulations from published data. Most of the formulations assessed reported cytotoxic and genotoxic damage, mainly those that lack of coating agent and the biogenically produced nanoparticles [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that cobalt oxide NPs induced DNA strand breaks and apoptosis. Also, NPs cause chromosomal aberrations as several researchers have discussed in their study of these effects in higher plants (Kumari et al, 2009;Ghosh et al, 2010;Landa et al, 2012;Mukherjee et al, 2016;Debnath et al, 2018).…”
Section: Description Concentration % Reference Low Highmentioning
confidence: 99%